2022
DOI: 10.1177/00031348221082292
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Perioperative Fluid Management in Complex Abdominal Wall Reconstruction to Prevent Postoperative Acute Kidney Injury

Abstract: Background Acute kidney injury (AKI) is a serious postoperative complication of abdominal wall reconstruction that can significantly impact outcomes of these patients. This study examines AKI following abdominal wall hernia repair to determine incidence and risk factors and outline potential mitigation strategies. Methods Using a single institution IRB-approved prospective database, patients undergoing complex abdominal wall reconstruction from 2013 to 2021 were identified. Patients with AKI were compared to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…reported that strict blood glucose control by an artificial endocrine pancreas during hepatectomy could prevent pAKI ( 42 ); Shelby et al. suggested that optimizing perioperative fluid management in patients who underwent complex abdominal wall reconstruction could prevent pAKI ( 43 ). However, more effective strategies to protect patients who underwent TAAD surgery from pAKI need further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that strict blood glucose control by an artificial endocrine pancreas during hepatectomy could prevent pAKI ( 42 ); Shelby et al. suggested that optimizing perioperative fluid management in patients who underwent complex abdominal wall reconstruction could prevent pAKI ( 43 ). However, more effective strategies to protect patients who underwent TAAD surgery from pAKI need further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective randomized controlled study conducted by Kamenshchikov et al demonstrated that nitric oxide delivery during cardiopulmonary bypass reduced pAKI (41). In terms of non-cardiac surgery, Mita et al reported that strict blood glucose control by an artificial endocrine pancreas during hepatectomy could prevent pAKI (42); Shelby et al suggested that optimizing perioperative fluid management in patients who underwent complex abdominal wall reconstruction could prevent pAKI (43). However, more effective strategies to protect patients who underwent TAAD surgery from pAKI need further exploration.…”
mentioning
confidence: 99%
“…In those with postoperative acute kidney injury (as defined by the Risk, Injury, Failure, Loss, and End-stage Kidney criteria), 5000 units of unfractionated heparin three times a day was used instead. 16 Patients were required to ambulate with assistance at least once on POD 0 and then required to ambulate with assistance five or more times each day thereafter. Dedicated physical therapy was ordered only in cases of baseline mobility issues.…”
Section: Perioperative and Intraoperative Managementmentioning
confidence: 99%